Factors Related to Sleep Quality in Final Semester Pharmacy Students of Mandala Waluya University - Cece Indriani; Muh. Afdhal Firdaus; Wa Ode Nova Noviyanti; Ahmad Yani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Sleep is a recovery process for the body and brain and is very important for achieving optimal health. Lack of sleep can cause students to become tired or easily tired, emotional instability, lack of self-confidence, excessive impulsiveness and carelessness. A preliminary study with 32 final year pharmacy students revealed that 32 said they experienced symptoms of irregular sleep patterns, stress, decreased appetite, anxiety and restlessness. Objective: This study aims to determine the relationship between stress, screen time, eating patterns and anxiety with sleep quality in final semester pharmacy students at Mandala Waluya University in 2024. Method: The type of research used in this research is quantitative with a cross sectional study design. The population in this study was 158 final semester pharmacy students at Mandala Waluya University. A sample of 62 respondents was obtained using simple random sampling techniques. The analysis method uses Fisher's Exact Test. Result: The statistical test results show that Stress obtained a value of p=0.004 and ? 0.05, namely 0.004 < 0.05, Screen Time obtained a value of p=0.004 and ? 0.05, namely 0.004 < 0.05, Eating Pattern obtained a value of p=0.001 and ? 0.05, namely 0.001 < 0.05, and Anxiety obtained a value of p = 0.000 and ? 0.05, namely 0.000 < 0.05. Conclusion: Suggestions for students are that they hope to be able to improve sleep quality well so that it does not hinder the lecture process, then for further research, it is highly recommended to use online questionnaires such as Google Forms or similar and use other variables such as disease, caffeine consumption and the environment.